Development of a new type of alcoholic ice cream - Kochubei-Lytvynenko, Oksana; Polishchuk, Galyna; Osmak (Fedchenko), Tetiana; Bass, Oksana; Mykhalevych, Artur (My University, 2021)
The modern range of milk-based ice cream with an alcohol component was analyzed. The choice of alcoholic tincture in the composition of milk ice cream was substantiated. The cryoscopic temperature of the mixtures was determined using a measuring complex, the dynamic viscosity was determined by a Heppler viscometer, the melting resistance was determined by the melting time of the hardened ice cream samples, and the ice cream was whipped by the weight method. The possibility of using tinctures with an alcohol content of 20% as a part of milk ice cream has been scientifically confirmed. The selection of the structure stabilizer and rational modes of maturation of milk-alcohol mixtures were substantiated by the values of the coefficient of dynamic viscosity. According to the cryoscopic temperature of ice cream mixtures, it was found that the production of ice cream with a mass fraction of alcohol up to 3% determines the possibility of using conventional freezing modes to obtain a product of guaranteed quality. A new type of milk ice cream with the use of tinctures can be recommended for the introduction of the classical technological scheme of production with the clarification of maturation modes.
Keywords: tinctures; ice cream; cryoscopic temperature; maturation; кафедра технології молока і молочних продуктів